Ablation of Zfhx4 results in early postnatal lethality by disrupting the respiratory center in mice. (20th January 2021) - Zhang, Meiqin; Du, Sichen; Ou, Huayuan; Cui, Renjie; Jiang, Nan; Lin, Yifeng; Ge, Runsheng; Ma, Duan; Zhang, Jin
Abstract: Breathing is an integrated motor behavior that is driven and controlled by a network of brainstem neurons. Zfhx4 is a zinc finger transcription factor and our results showed that it was specifically expressed in several regions of the mouse brainstem. Mice lacking Zfhx4 died shortly after birth from an apparent inability to initiate respiration. We also found that the electrical rhythm of brainstem‒spinal cord preparations was significantly depressed in Zfhx4 -null mice compared to wild-type mice. Immunofluorescence staining revealed that Zfhx4 was coexpressed with Phox2b and Math1 in the brainstem and that Zfhx4 ablation greatly decreased the expression of these proteins, especially in the retrotrapezoid nucleus. Combined ChIP‒seq and mRNA expression microarray analysis identified Phox2b as the direct downstream target gene of Zfhx4, and this finding was validated by ChIP‒qPCR. Previous studies have reported that both Phox2b and Math1 play key roles in the development of the respiratory center, and Phox2b and Math1 knockout mice are neonatal lethal due to severe central apnea. On top of this, our study revealed that Zfhx4 is a critical regulator of Phox2b expression and essential for perinatal breathing.